Pentingnya Sertifikat Laik Fungsi Di Rumah Sakit: Literature Review - Pupu Pujiawati; Eufemia Maria; Shony Mandala; Vip Paramarta (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
A Building functional certificate, hereinafter referred to as SLF, is a certificate issued by the regional government except for special function buildings by the central government, to state the building's functional fitness as a condition for it to be utilized. Based on Minister of Health Regulation Number 40 of 2022 concerning technical requirements for hospital buildings, infrastructure and health equipment in article 1, the regulation of technical requirements for hospital buildings, infrastructure and health equipment aims to create functional hospital buildings, infrastructure and health equipment. Referring to the regulations above, hospital buildings must meet the requirements for safety, health, comfort, convenience, efficient use of resources, harmony and harmony with their environment, realizing orderly, effective and efficient hospital building management. This literature review was made to include journals published in Indonesian, journals published in the 2022-2023 period regarding certificates of functional fitness for hospital buildings, especially regarding the requirements for fulfilling certificates of functional fitness in hospitals. After going through screening, inclusion and exclusion criteria, 3 articles were analyzed. As a result, hospitals need to adjust permits and proper functioning of buildings in accordance with new regulations, then hospitals are expected to follow new regulatory updates in order to maintain the security and safety of patients, visitors and hospital employees from unexpected events.